A simple, rapid procedure for the isolation of DNA for PCR from Gibberella fujikuroi (Fusarium section Liseola) - N. M. DuTEAU; J. F. LESLIE (Fungal Genetics Reports, 1991)
The polymerase chain reaction (PCR) is a method for amplifying specific segments of DNA defined by the small primers used to start the reaction. Using arbitrarily chosen 10-base primers, one can generate "random amplified polymorphic DNA" (RAPD) markers (Williams et al. 1991 Nucl. Acids Res. 18:6531-6535). These DNA fragments, separated by electrophoresis in an agarose gel, can be used as markers for studying genetic variation within and among fungal populations.